IMPLEMENTASI MODEL PEMBELAJARAN TWO STAY TWO STRAY UNTUK MENINGKATKAN LITERASI DAN BERPIKIR KRITIS SISWA MADRASAH IBTIDAIYAH - Midya Yuli Amreta; Khofifah Indar Lutfiani; Alfi Fakhriyyatun Nisrina; Siti Lutfiatul Muhamaliah; Ika Devi Ratna Ning Tias; Ilma Alfiyanti; M. Hasan Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Facing the challenges in the 21st century era marked by globalization and the Industrial Revolution 4.0, literacy and critical thinking skills are fundamental competencies for students. Students at MIN 1 Bojonegoro who are known to be active and intelligent, need a learning model that can optimize this potential. The objective of this research was to explore how effectively the Two Stay Two Stray (TSTS) cooperative learning model fosters students' literacy and critical thinking skills, while also providing actionable insights for teaching practice. Utilizing a qualitative descriptive method, the study was conducted as a case study at MIN 1 Bojonegoro. Data collection techniques included observation, interviews, and document analysis. The results indicate that the TSTS model plays a substantial role in enhancing both literacy and critical thinking among students. With the right preparation and support, TSTS can be an effective method for producing students who are not only academically accomplished, but also literate, critical, collaborative, and ready to face global challenges.